ETHICAL CONSIDERATIONS IN USE OF ARTIFICIAL INTELLIGENCE IN DIGITAL MARKETING - Etizaz Ali; Dr. Muhammad Riaz; Muhammad Rashid (Journal of Peace, Development and Communication, 2024)
Digital marketing has achieved new levels of success due to its integration with Artificial Intelligence (AI). Digital marketers are now able to analyze the huge amount of customers’ data with the help of AI. Moreover, AI can make decisions based on that analysis which consequently helps the digital marketers to achieve their objectives. The purpose of this study was to highlight the ethical considerations in the use of AI in digital marketing primarily focusing on the process of transparency, customers’ privacy, fairness, and accountability. In this study the concerned literature and case studies were reviewed to assess potential risks and make recommendations to improve the protection of customers’ data. This study provides insight to the marketers that while benefiting from AI in digital marketing; they have to respect the customers’ rights and make it as a routine part of their decision making and implementation. This study explored the customers’ concerns about their privacy and decision making in digital markets and generated awareness about collection of users’ data process and need of transparency, fairness, and accountability.